Age-Related Differences in the Effects of Masker Cuing on Releasing Chinese Speech From Informational Masking - Feng, Tianquan; Chen, Qingrong; Xiao, Zhongdang (Frontiers in Psychology, 2018)
The aims of the present study were to examine whether familiarity with a masker improves word recognition in speech masking situations and whether there are age-related differences in the effects of masker cuing. Thirty-two older listeners (range = 59-74; mean age = 66.41 years) with high-frequency hearing loss and 32 younger normal-hearing listeners (range = 21-28; mean age = 23.73) participated in this study, all of whom spoke Chinese as their first language. Two experiments were conducted and 16 younger and 16 older listeners were used in each experiment. The masking speech with different content from target speech with syntactically correct but semantically meaningless was a continuous recording of meaningless Chinese sentences spoken by two talkers. The masker level was adjusted to produce signal-to-masker ratios of -12, -8, -4, and 0 dB for the younger participants and -8, -4, 0, and 4 dB for the older participants. Under masker-priming conditions, a priming sentence, spoken by the masker talkers, was presented in quiet three times before a target sentence was presented together with a masker sentence 4 s later. In experiment 1, using same-sentence masker-priming (identical to the masker sentence), the masker-priming improved the identification of the target sentence for both age groups compared to when no priming was provided. However, the amount of masking release was less in the older adults than in the younger adults. In experiment 2, two kinds of primes were considered: same-sentence masker-priming, and different-sentence masker-priming (different from the masker sentence in content for each keyword). The results of experiment 2 showed that both kinds of primes improved the identification of the targets for both age groups. However, the release from speech masking in both priming conditions was less in the older adults than in the younger adults, and the release from speech masking in both age groups was greater with same-sentence masker-priming than with different-sentence masker-priming. These results suggest that both the voice and content cues of a masker could be used to release target speech from maskers in noisy listening conditions. Furthermore, there was an age-related decline in masker-priming-induced release from speech masking.